[Letters to General Ne Win] - ʾOnʻ Krīʺ, Bhulʻ Mhūʺ Khyupʻ; Ne Vaṅʻʺ, Ūʺ, 1911- (1988)
Print out of a collection of letters by a retired senior army officer and close confidante of General (Retired) Ne Win, then head of state in Burma, during the 1988 democracy uprising. Dates of the letters included in the collection are March 7 (in English), May 9 (in Burmese and English translation; one page missing from English), and June 8 (in handwritten Burmese and English translation).
Author: Brigadier General (Retired) Aung Gyi.
Title devised by cataloguer.
Some contents indistinct.
Also available in an electronic version via the Internet, viewed on 20/6/2011: http://asiapacific.anu.edu.au/newmandala/wp-content/uploads/2011/06/AungGyiLetters.pdf
In Burmese and English.
Keywords: Burma -- Politics and government -- 1988-.; Burma -- History -- 1988-.